Family Practices To Address Mercury Contamination Or Poisoning (International Journal of Environmental Sciences, 2025)
Artisanal gold mining in the lower San Jorge River basin in Córdoba has generated severe environmental and health impacts due to the use of mercury. Objective: To analyze family practices to address mercury contamination or poisoning. A qualitative, ethnographic, and descriptive approach was adopted to explore families' experiences and perceptions. Methodology: Fieldwork included direct observations, interviews, focus groups, and analysis of field diaries, following the methods of Hammersley and Atkinson. The research considers the meanings attributed by communities to their daily practices and how these are influenced by social, cultural, and economic factors. Results: Families employ traditional knowledge and cultural adaptations to reduce mercury exposure. These strategies include the use of informal preventive practices and the incorporation of local beliefs into their risk management. Social dynamics that facilitate or constrain the adoption of preventive measures were identified. Conclusions: The findings underscore the importance of integrating local knowledge into the design of public health strategies to mitigate mercury exposure. These interventions must be culturally sensitive, sustainable, and focused on strengthening communities' capacity to manage environmental risks.